The Differences Of Reasoning Ability And Understanding Of Mathematics Concepts Teached With The CORE And CRH Learning - Febriani, Luly (Yana Research, 2022)
This study aims to determine the differences in mathematical reasoning abilities and understanding of mathematical concepts of students who are taught with the CORE learning model and the CRH learning model in class XI MAS Darul Akhirah. This research is a quantitative research with a quasi-experimental type of research. The population in this study were all students of class XI MAS Darul Akhirah. The academic year 2020/2021 consisted of three classes and totaled 70 students. the sample in this study was class XI IPS 1 totaling 28 students and class XI IPS 2 totaling 27 students. the test instrument used to determine the reasoning ability and understanding of students' mathematical concepts by using a descriptive form test. Data analysis was performed by analysis of variance (ANOVA). the findings show : 1). Mathematical reasoning ability and understanding of mathematical concepts of students taught with the CORE learning model were not better than students taught with the CRH model in arithmetic sequences and series. obtained f count (3,307) < f table (3,93);2). the mathematical reasoning ability of students who are taught by the CORE learning model is not better than students who are taught by the CRH model, it is obtained that f count (2.481) < f table (4.023), 3). the ability to understand concepts taught by the CORE model is not better than students who are taught by the CRH model, it is obtained that f count (3.035) < f table (4.023). The conclusion in this study explains that there is no difference in mathematical reasoning ability and understanding of mathematical concepts of students who are taught with the CORE and CRH models.